The Nongenomic Effects of Progesterone in Repressing iNOS Activation through P38MAPK Pathways in Gonococci-Infected Polymorphonuclear Leukocytes and the Clinical Significance - 陈嵘祎 涂亚庭 林加西 佘惟槟 李娟 吴志洪 许莉 陈宏翔 (Journal of Huazhong University of Science and Technology. Medical sciences, 2010)
Progesterone has nongenomic effects on inducible nitric oxide synthase(iNOS),which is mediated by mitogen activated protein kinase(MAPK)pathways.This effect is supposed to have some potential association with asymptomatic gonococcal infections in women by immunological depression.In this study,polymorphonuclear leukocytes(PMNs)challenged by gonococci were used to study the nongenomic effects of progesterone.The activation of iNOS was assessed by measuring [3H] L-arginine converses to [3H] L-citrulline,and t...